Association between bullying behavior, perceived school safety, and self‐cutting: a Japanese population‐based school survey. Issue 3 (25th November 2016) - Hamada, Shoko; Kaneko, Hitoshi; Ogura, Masayoshi; Yamawaki, Aya; Maezono, Junko; Sillanmäki, Lauri; Sourander, Andre; Honjo, Shuji
Abstract : Background: No previous population‐based studies have examined associations between self‐cutting, perceived school safety, and bullying behavior among East Asian adolescents. Method: We examined whether bullying, victimization, and perceived school safety were associated with self‐cutting by getting 1865 students with a mean age of 13.9 years (standard deviation 0.2 years) to complete questions on these variables. Psychiatric problems were assessed with the Strengths and Difficulties Questionnaire. Results: About 5.6% of males and 11.9% females had practiced self‐cutting and when we controlled these results for psychiatric symptoms, self‐cutting was associated with being both a bully and a victim among males and females. In addition, self‐cutting was independently associated with perceived school safety among females. Those who felt unsafe at school and were victimized were much more likely to engage in self‐cutting. Conclusions: Self‐cutting among Japanese adolescents was linked with bullying behavior and feeling unsafe at school. Secure school environments and school‐based antibullying programs could help to prevent adolescent self‐injurious behavior.